Influence of Smoking Dosage and Chronic Obstructive Lung Disease on the Incidence of Appropriate Therapies and Mortality in Patients with Structural Heart Disease and an Implantable Cardioverter Defibrillator. Issue 1 (8th September 2014) - KREUZ, JENS; SKOWASCH, DIRK; KAMRATH, PHILIP; LORENZEN, HENNING; TIYERILI, VEDAT; LINHART, MARKUS; NICKENIG, GEORG; SCHWAB, JÖRG O.
<x xml:space="preserve">Abstract</x> Background Smoking is known as a relevant risk factor for severe cardiac morbidities and mortality. This study was initiated to explore the influence of smoking dosage and presence of chronic obstructive lung disease (COPD) on the incidence of appropriate implantable cardioverter defibrillator (ICD) interventions and on mortality. Methods Prior studies on patients equipped with an ICD suggested that nicotine consumption increases the risk of experiencing an appropriate ICD therapy. There is no substantial data regarding the influence of cigarette smoking dosage on overall mortality in such endangered patients. A total of 349 patients with structural heart disease, either coronary artery disease or nonischemic cardiomyopathy equipped with an ICD, were included. Every patient answered a questionnaire regarding his smoking status and performed a spirometry and body plethysmography. Results A total of 104 patients (30%) suffered from COPD. Fifty‐eight patients (17%) were "current smokers, " 196 patients (56%) were revealed as "former smokers, " while 93 (27%) patients were registered as "never smokers." A total of 163 patients (47%) received at least one appropriate ICD intervention during follow‐up (median 48 ± 8 months). Twenty‐three patients died during this study (6.6%). There was no association of COPD with the incidence of appropriate ICD therapies or mortality. Smoking dosage revealed as a significant risk factor for both appropriate ICD interventions (hazard ratio [HR] 1.5 for 60 pack years [PY] P = 0.04) and mortality (HR 2.3 for 60 PY P = 0.02). Conclusion This study demonstrates a dose‐related increased risk of smokers for appropriate ICD interventions and mortality. The results of this trail urge a strict nicotine abstinence, especially in patients with a structural heart disease undergoing ICD therapy.